Hubungan Remunerasi dan Motivasi Kerja dengan Kepuasan Kerja Perawat di RS PKU Muhammadiyah Gamping - Elmira Apriliani; Nur Hidayah (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Remuneration or reward, which is part of compensation management, may affect the morale and motivation of employees to do a better work performance. This research aimed to analyze the correlation between remuneration and work motivation with nurses’ job satisfaction in PKU Muhammadiyah Gamping Hospital. This study was a quantitative one with cross sectional approach. The sample of this study consisted of 123 nurses which was selected using proportional random sampling method. Questionnaires were used to gather data and the result analyzed with path analysis method. The result showed that remuneration variable had a positive and significant influences on nurses’ job satisfaction (p=0,007), work motivation (p=0,003) while work motivation had a positive significant influences on nurses’ job satisfaction (p=0,001). The result of path analysis indicated that the direct influence of remuneration on nurses’ job satisfaction is higher compared to its indirect influence. Optimalization of nurses’ work motivation and job satisfaction on the implementation of a professional nursing care in PKU Muhammadiyah Gamping hospital can be improved by adjusting the remuneration or compensation of their work services.